Changes in colorectal cancer incidence in seven high-income countries: a population-based study. (July 2019) - Araghi, Marzieh; Soerjomataram, Isabelle; Bardot, Aude; Ferlay, Jacques; Cabasag, Citadel J; Morrison, David S; De, Prithwish; Tervonen, Hanna; Walsh, Paul M; Bucher, Oliver; Engholm, Gerda; Jackson, Christopher; et al.
Summary: Background: The overall incidence of colorectal cancer is decreasing in many high-income countries, yet analyses in the USA and other high-income countries such as Australia, Canada, and Norway have suggested increasing incidences among adults younger than 50 years. We aimed to examine longitudinal and generational changes in the incidence of colon and rectal cancer in seven high-income countries. Methods: We obtained data for the incidence of colon and rectal cancer from 20 population-based cancer registries in Australia, Canada, Denmark, Norway, New Zealand, Ireland, and the UK for the earliest available year until 2014. We used age–period–cohort modelling to assess trends in incidence by age group, period, and birth cohort. We stratified cases by tumour subsite according to the 10th edition of the International Classification of Diseases. Age-standardised incidences were calculated on the basis of the world standard population. Findings: An overall decline or stabilisation in the incidence of colon and rectal cancer was noted in all studied countries. In the most recent 10-year period for which data were available, however, significant increases were noted in the incidence of colon cancer in people younger than 50 years in Denmark (by 3·1%; per year), New Zealand (2·9% per year), Australia (2·9% per year), and the UK (1·8% per year). Significant increases in the average annual percentage change in the incidence of rectal cancer were also noted in this age group in Canada (by 3·4% per year), Australia (2·6% per year), and the UK (1·4% per year). Contemporaneously, in people aged 50–74 years, the average annual percentage change in the incidence of colon cancer decreased significantly in Australia (by 1·6% per year), Canada (1·9% per year), and New Zealand (3·4% per year) and of rectal cancer in Australia (2·4% per year), Canada (1·2% per year), and the UK (1·2% per year). Increases in the incidence of colorectal cancer in people younger than 50 years were mainly driven by increases in distal (left) tumours of the colon. In all countries, we noted non-linear cohort effects, which were more pronounced for rectal than for colon cancer. Interpretation: We noted a substantial increase in the incidence of colorectal cancer in people younger than 50 years in some of the countries in this study. Future studies are needed to establish the root causes of this rising incidence to enable the development of potential preventive and early-detection strategies. Funding: Canadian Partnership Against Cancer, Cancer Council Victoria, Cancer Institute New South Wales, Cancer Research UK, Danish Cancer Society, National Cancer Registry Ireland, the Cancer Society of New Zealand, NHS England, Norwegian Cancer Society, Public Health Agency Northern Ireland, Scottish Government, Western Australia Department of Health, and Wales Cancer Network.